2017
DOI: 10.15570/actaapa.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Restoring facial symmetry through non-surgical cosmetic procedures after permanent facial paralysis: a case report

Abstract: Facial nerve paralysis can occur due to infection, inflammation, trauma, surgery, and tumors. It leads to facial asymmetry, impaired oral competence, articulation deficits, and psychological problems. Treatment options include physical therapy, static slings, nerve and muscle transfers, blepharoplasty, brow lift, and chemodenervation with botulinum toxin. We report the case of a 66-year-old Caucasian female with permanent facial paralysis following middle ear surgery. The facial asymmetry was treated successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…HA fillers and BoNTA can be used in patients with facial palsy to correct asymmetries. The treatment improves function of the lips and esthetics 39,40 . In a recent trial, it could be demonstrated that the patients benefit also in their psycho‐social well‐being 41 …”
Section: Fillers and Botulinum Toxin To In Rehabiliation After Permanmentioning
confidence: 99%
“…HA fillers and BoNTA can be used in patients with facial palsy to correct asymmetries. The treatment improves function of the lips and esthetics 39,40 . In a recent trial, it could be demonstrated that the patients benefit also in their psycho‐social well‐being 41 …”
Section: Fillers and Botulinum Toxin To In Rehabiliation After Permanmentioning
confidence: 99%
“…Compared to surgery, they provide facial rejuvenation and aesthetic enhancement at a lower cost, with less complications, minimal downtime, and immediate results. Although HA injections are excellent tools utilized in facial cosmetic improvements, they could also be applied to treat facial deformities resulting from traumatic events, orbital and periorbital surgeries, tumor resections, congenital deformities, burns, scars, and facial palsy [8][9][10][11]. Injective techniques could also be utilized for HIV-related facial lipoatrophy or progressive hemifacial atrophy [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, few papers have raised the attention to a most comprehensive aesthetic approach in facial restoration in case of congenital or acquired (trauma, tumor resection) anomalies [1][2][3]. WHO's definition of health, "a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity," clearly underlines how important is, especially for the facial area, a complete aesthetic restoration also in patients treated for noncosmetic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…SFG is a surgical procedure standardized by Coleman and largely used for cosmetic and reconstructive purposes [4]. His primary indication was "to fill a gap," although further studies have shown also a regenerative effect related to the preadipocytes present in the lipoaspirate [4]; also, nonsurgical cosmetic procedures, such as botulinum toxin type A and HA fillers, have been described to treat or improve symmetry in facial nerve injury [1].…”
mentioning
confidence: 99%